2007
DOI: 10.1529/biophysj.106.100891
|View full text |Cite
|
Sign up to set email alerts
|

Weak Self-Association in a Carbohydrate System

Abstract: The physiological importance of weak interactions between biological macromolecules (molar dissociation constants >10 microM) is now well recognized, particularly with regard to cell adhesion and immunological phenomena, and many weak interactions have been measured for proteins. The concomitant importance of carbohydrate-carbohydrate interactions has also been identified, although no weak interaction between pure carbohydrate systems has ever been measured. We now demonstrate for the first time to our knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 67 publications
2
39
0
1
Order By: Relevance
“…hemoglobin), or higher-order reversible association products (tubulin, viral coat proteins, sickle cell hemoglobin), with clear functional roles that have never been observed for carbohydrates. Although weak self-association in a polysaccharide has been shown, [1] we show for the first time the presence of multiple oligomeric forms in a whole class of polymeric carbohydrates, 6-deoxy-6-aminocelluloses, using the hydrodynamic technique of analytical ultracentrifugation as a probe.Water-soluble aminocelluloses were prepared by the reaction of tosyl cellulose with an excess of di-or trifunctional amines, namely with tris(2-aminoethyl)amine yielding 6-deoxy-6-(2-(bis(2-aminoethyl)aminoethylamino) (BAEA) cellulose (1-3), as depicted in Figure 1. Similar structures were obtained from reactions of tosyl cellulose with 1,2-diaminoethane and 4,7,10-trioxa-1,13-tridecandiamine to give 6-deoxy-6-(2-aminoethyl)amino (AEA) cellulose 4 and 6-deoxy-6-(13-amino-4,7,10-trioxatridecaneamino) (ATOTA) cellulose 5, respectively (Supporting Information Figure 1).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…hemoglobin), or higher-order reversible association products (tubulin, viral coat proteins, sickle cell hemoglobin), with clear functional roles that have never been observed for carbohydrates. Although weak self-association in a polysaccharide has been shown, [1] we show for the first time the presence of multiple oligomeric forms in a whole class of polymeric carbohydrates, 6-deoxy-6-aminocelluloses, using the hydrodynamic technique of analytical ultracentrifugation as a probe.Water-soluble aminocelluloses were prepared by the reaction of tosyl cellulose with an excess of di-or trifunctional amines, namely with tris(2-aminoethyl)amine yielding 6-deoxy-6-(2-(bis(2-aminoethyl)aminoethylamino) (BAEA) cellulose (1-3), as depicted in Figure 1. Similar structures were obtained from reactions of tosyl cellulose with 1,2-diaminoethane and 4,7,10-trioxa-1,13-tridecandiamine to give 6-deoxy-6-(2-aminoethyl)amino (AEA) cellulose 4 and 6-deoxy-6-(13-amino-4,7,10-trioxatridecaneamino) (ATOTA) cellulose 5, respectively (Supporting Information Figure 1).…”
mentioning
confidence: 74%
“…[3] Sedimentation coefficients were extrapolated to zero concentration to correct for non-ideality effects. [1] …”
Section: Methodsmentioning
confidence: 99%
“…Arabinoxylans (Patel, et al, 2007) too have recently been characterised, but konjac glucomannan (KGM) has not been so well described. This conducted study aims to fill these gaps in our knowledge before the behaviour of the protein-polysaccharide mixtures are properly investigated.…”
Section: <Figure 1 Here>mentioning
confidence: 99%
“…Proteins can also self-associate strongly and weakly (van der Merwe & Barclay, 1994) and polysaccharides can form strong self-aggregation complexes. A recent study by Patel et al (2007) showed that they can even interact with each other weakly with interaction strengths resembling those of molecules involved with cell-cell recognition and signalling, with molar dissociation constant K d ~ 100 µM.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric micelles are widely used as nanocarriers for drug, protein, or gene delivery. In addition, in aqueous solutions carbohydrates and oligosaccharides self-associate to form aggregates [3]. Cyclodextrins (CDs), which are cyclic oligosaccharides consisting of six or more a-l,4-linked d-glucopyranose units, are used as enabling excipients in numerous marketed drug formulations.…”
Section: Introductionmentioning
confidence: 99%